Therapeutic targets on toxoplasma gondii parasite in combatting toxoplasmosis - Abdullahi, Sharif Alhassan; Unyah, Ngah Zasmy; Nordin, Noshariza; Basir, Rusliza; Mohammed Nasir, Wana; Ahmad Alapid, Ashraf; Hassan, Yahaya; Mustapha, Tijjani; Abd Majid, Roslaini (Sciencedomain International, 2019)
The status of toxoplasmosis management is challenged by drug intolerance, compromised efficacy and potential development of drug resistance. However, currently, there are very limited targets on T. gondii that serve as the site of action of current medications. This review aimed to explore more potential targets that are essential to parasite survival and are absent in humans. Many unexplored targets on T. gondii exist and their specificities to the parasite make them ideal drug targets. The present review had searched relevant English databases such as PubMed, Scopus, Google scholar and Science Direct, for relevant literature on the therapeutic target of T. gondii. Many of the enzyme systems in several pathways are essentially palatable as drug targets. Establishing compounds that can target these enzymes on T. gondii will greatly be beneficial in treating acute and chronic toxoplasmosis in humans.